LANGUAGE TEACHING TO MILITARY STUDENTS IN UZBEKISTAN - Khamidova Nigora Tulkunovna (Scholar Express Journal, 2023)
This article examines the nuanced landscape of language teaching to military students in Uzbekistan, offering insights into the vital role of linguistic proficiency within the armed forces and its broader implications for national security. The introduction underscores the diverse linguistic tapestry of Uzbekistan, emphasizing the necessity for military personnel to navigate multiple languages. Section 1 explores the critical importance of language proficiency in military operations, diplomatic engagements, and international collaborations. It delves into the operational and diplomatic advantages of linguistic versatility, shedding light on its role in building cultural bridges and fostering regional alliances. The subsequent sections will delve into tailored language teaching approaches, challenges faced, success stories, and future recommendations, providing a comprehensive exploration of language education within the unique context of the Uzbekistani military.
Keywords: Military service; linguistic versatility; language teaching